Coherence‐adjustable, high‐directional, electrically pumped semiconductor lasers around 650 nm. Issue 5 (5th March 2023) - Liu, Lingjuan; Wang, Yufei; Ji, Haiyang; Fu, Ting; Zheng, Wanhua
Abstract: By fabricating patterned electrodes on a dumbbell‐shaped cavity semiconductor laser, the coherence of the laser can be switched by only changing the injection current. The threshold current and the peak power of the laser are 0.75 A and 1.41 W @ 3 A. Under the injection of small and large currents, the measured speckle contrasts are 40.0% @ 0.8 A and 7.0% @ 3 A. And the corresponding horizontal far‐field divergence angles are 4.05° and 8.7°, respectively, showing a high directionality. Such a laser with a wide range of adjustable coherence and a high directionality has a great potential in the field of bioimaging. Abstract : The authors realized a coherence‐adjustable and highly directional semiconductor laser around 650 nm. Such semiconductor lasers have great potential for bioimaging.